Adult granulosa cell tumour‐like areas occurring in ovarian epithelial neoplasms: report of a case series with investigation of FOXL2 mutation status. Issue 5 (12th December 2013) - Singh, Naveena; Gilks, C Blake; Huntsman, David G; Smith, John H; Coutts, Michael; Ganesan, Raji; McCluggage, W Glenn
<x xml:space="preserve">Abstract</x> Aims To look for FOXL2 mutation in rare ovarian epithelial lesions showing stromal components with morphological features of adult granulosa cell tumour (AGCT). Methods and results We report the 402C→G FOXL2 mutation status in five epithelial ovarian lesions in women aged 45–77 years showing stromal proliferations that were morphologically indistinguishable from AGCT. The lesions were mucinous cystadenoma, mixed epithelial cystadenoma, endometriotic cyst, mucinous borderline tumour (intestinal type), and mucinous carcinoma. In one case, the AGCT component formed a discrete nodule, and in the others it was distributed within the septa and cyst walls. FOXL2 mutation was present in two cases and absent in three cases. One mutation‐positive case showed an AGCT nodule abutting a mucinous borderline tumour, interpreted as a collision tumour. The other positive case had an AGCT component within the septa of a mucinous carcinoma, and both components are likely to be neoplastic. In the three cases without FOXL2 mutation, the stromal component most likely represents a non‐neoplastic AGCT‐like proliferation. Conclusions Areas typical of AGCT are rarely associated with epithelial ovarian lesions. These are heterogeneous and likely to be truly neoplastic in only a subset of cases. FOXL2 mutation testing may be useful in confirming a true neoplastic AGCT component.